Corneal trauma induced by a pumpkin root - Głowacka, Aleksandra; Kożuchowska, Anna; Babińska, Marta; Konopińska, Joanna; Saeed, Emil (Klinika Oczna / Acta Ophthalmologica Polonica, 2025)
Corneal trauma may be induced by a foreign body injury. A penetrating injury can lead to corneal infections, which is why it is paramount to provide immediate help to an injured patient and implement proper treatment. It is possible that infection occurs despite treatment. To determine the pathogen responsible for the infection, a conjunctival swab should always be taken. Infection may not only be caused by the usual pathogens recognized worldwide, but opportunistic infections, such as those of fungal origin, Acremonium sp., especially in immunosuppressed patients, may also occur. A 62-year-old patient suffered a corneal injury while gardening in the left eye. Acremonium sp. infection led to keratomycosis, which resulted in the patient’s gradual deterioration of vision. The patient was admitted for urgent care three months after injury, complaining of severe pain and vision loss. The slit lamp examination showed inflammatory exudate in the anterior chamber and an opaque cornea. A therapeutic corneal transplant was performed and the patient was under continuous hospital care. However, the patient’s state improved, after three months of continued antibiotherapy and steroid therapy, there was a reinfection of Acremonium sp. Regarding sudden deterioration of the patient’s vision and painful eye, enucleation was performed. Acremonium sp. is becoming a more common pathogen in ocular infections. It is worth noting that every corneal injury may result in an infection difficult to control and must be treated. When it is unmanageable, the implementation of surgical treatment may be optimal for the patient.